Design of a thin disk amplifier with extraction during pumping for high peak and average power Ti Sa systems (EDP-TD) - Chvykov Vladimir (OPTICS EXPRESS, 2016)
Combination of the scheme of extraction during pumping (EDP) and the Thin Disk (TD) technology is presented to overcome the limitations associated with thermal cooling of crystal and transverse amplified spontaneous emission in high average power laser systems based on Ti: Sa amplifiers. The optimized design of high repetition rate 1-10 PW Ti: Sapphire EDP-TD power amplifiers are discussed, including their thermal dynamic behavior. (C) 2016 Optical Society of America